Different Forms of Ghrelin Exhibit Distinct Biological Roles in Tilapia - Riley, Larry (Frontiers in Endocrinology, 2013)
Ghrelin has been identified in all vertebrate classes, including sharks. Each species possesses multiple forms of ghrelin that vary in peptide length and acyl modifications (e.g., n-hexanoic, n-non-anoic, n-octanoic, and n-decanoic acids) including des-acyl ghrelin. Octanoylated ghrelin has been shown to be a potent GH secretagogue, orexigenic factor, and plays a role in overall metabolism in vertebrates. In the tilapia model, octanoylated ghrelin (ghrelin-C8) and decanoylated ghrelin (ghrelin-C10) exhibit different biological actions. This mini review highlights the current knowledge of the differential actions of ghrelin-C8 and ghrelin-C10 from studies in the tilapia model. These findings suggest that the multiple forms of ghrelin may exhibit distinct yet complimentary actions directed toward maintaining overall energy balance in other vertebrates.